#TITLE_ALTERNATIVE# - (NIM 13205186), PRADIPTA
For this final year project, ANC is used to reduce the noise caused by a loom in a textile factory. The implementation of the ANC system used a TMS320C6713 DSP Starter Kit with FXLMS adaptive algorithm. The research in the laboratory was done before implemented the ANC system in the factory. During the research, a loudspeaker acts as the source of recorded loom noise. The research itself included FXLMS algorithm simulation using MATLAB 7, secondary path modeling with LMS algorithm, noise control using both single channel and multichannel structures with FXLMS algorithm. Centralized and Decentralized systems were used in the multichannel ANC system.